Comparison of The China-Vietnam-Indonesia Guerrilla War In The Perspective of The Universal War - Devis Lebo; I Wayan Midhio; Lukman Yudho Prakoso (Syntax Corporation Indonesia, 2021)
The history of war in several countries proves that universal war is a reliable strategy to win a battle. This universal war is used by weak military forces by utilizing national resources to fight against stronger and more modern forces in weaponry, as was done by China, Vietnam and Indonesia. War is caused by several factors, among others, psychological, cultural, ideological, economic and political. In writing this literature review, the author uses methods and theories by collecting data and information through the help of various materials contained in literature (books) or also known as phenomological research types associated with qualitative descriptive and defense philosophy. From the results of literature research, the writer finds that the universal war waged by each country that has adopted this strategy is different in its implementation and the objectives to be achieved. However, the universal war that has been carried out has brought very good results in accordance with the objectives of the struggle of each country that has used it.